The onion field [videorecording (DVD)] - Savage, John, 1949-; Woods, James, 1947-; Seales, Franklyn, 1952-1990; Wambaugh, Joseph (KL studio classics., 2015)
A true story about a case that changed LAPD policies forever. Two plainclothes LAPD officers were abducted and one was brutally executed, the other escaped. The criminals managed to drag the justice process on for years.